The Influence of Principal’s Leadership and Professional Teacher’s Competence on Teacher’s Performance - Fitria, Happy; Ahyani, Nur; Mahasir, Mahasir; Hermalita, Hermalita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study was conducted at SD Negeri Sukarami District, Palembang City. The purpose of this study was to determine the effect of principal’s leadership and teacher’s professional competence on teacher’s performance. The method in this study is a quantitative descriptive. The sample consisted of 44 elementary school teachers in Sukarami District, Palembang City. From the results of the data analysis that has been done, it is concluded that the leadership of the principal can influence teacher’s performance in the learning process. This is based on the results of the linearity test, as well as the teacher’s professional competence on teacher’s performance. Then there is a significant influence between the principal’s leadership and the teacher’s professional competence simultaneously on teacher’s performance, meaning that Ho is rejected and Ha is accepted.